Implementasi Kebijakan Program Balai Pelatihan Vokasi dan Produktivitas Terhadap Peningkatan Sumber Daya Manusia di Kabupaten Bantaeng - Saputra, Sakral Wijaya (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The purpose of the study was to determine the implementation of the vocational training and productivity program policy towards improving human resources in Bantaeng Regency. This research was conducted in Bantaeng Regency on July 15-20, 2024. The type of research is descriptive qualitative. Descriptive research is research with data collected in the form of words, pictures, and not numbers. The results of the study indicate that training programs that are in accordance with the needs of the local industry, BPVP can increase worker potential, support economic growth, and strengthen skills relevant to the labor market in accordance with Bantaeng Regency Regional Regulation Number 2 of 2015 concerning the Implementation of Job Training and Productivity stated in Article 6 paragraph (1) the implementation of job training is based on three main pillars, namely work competency standards, competency-based job training and competency certification. The role of the Bantaeng Regency Vocational Training and Productivity Center in human resource management is to provide training to the community in Bantaeng Regency. The training programs that are run are the result of human resource planning efforts. The purpose of this training program is to produce quality workers in the future.